Nitrogen stress induced changes in root system architecture (RSA) in diverse wheat (T. aestivum L.) genotypes at seedling stage - Nagar, Chetan Kumar, Gayatri; Bharati, Alka; Sinha, Subodh Kumar; Venkatesh, K; Mandal, Pranab Kumar (Journal of Cereal Research, 2018)
Improvement of Nitrogen use efficiency (NUE) in field crops is very important for reducing the cost of production, sustainable agriculture, reduce energy consumption for the production of chemical fertilizer and mitigates the environment pollution. It is more so in case of major cereals like wheat, where the NUE is 40%. N Uptake, assimilation, utilization and remobilization are the components of NUE. N Utilization by shoot primarily depends on available resources which in turn determine by N uptake by root system. Amount of N forage by different genotype under different N regime is primarily determined by Root System Architecture (RSA) and transporters.Here in this study, we are reporting a procedure of comparing N uptake in relation to root development and biomass among nine diverse genotypes of wheat seedling under N-stress and N-optimum condition. Biomass analysis showed significant increase in root dry weight due to N-stress in genotype HD-2967. In general shoots biomass reduced under N-stress condition. VL-401 exhibited significantly higher N-uptake under N-stress condition, where as it was least in case of GW-322 followed by Kalyansona. Fifteen RSA parameters were analyzed for all the nine genotypes, under both N-stress as well as N-optimum condition. All the RSA parameters except number of Forks and 2nd Order LR number showed higher values in N-stress as compare to N-optimum condition. However, six parameters namely TRS, PA, SA,Root volume,Main total length, and first order length increased significantly. Present study also identified two most contrasting genotypes VL-401 and WH-147 based on RSA.DOI:10.25174/2249-4065/2018/81209